2007
DOI: 10.1021/ma071803a
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Linear Chain−Ring Transition and Crystallization of Living Polymer Sulfur

Abstract: Deformation-induced crystallization of living polymer sulfur was studied with in situ wide-angle X-ray scattering, where chain scission plays a critical role. The onset of crystallization always occurs at the minimum stress point after the yield point, though different drawing rates were applied. With large drawing rates, deformation effect dictates the chain scission and linear chain-ring transition, which leads to the formation of linear chain fibrous phase, while only cyclooctasulfur crystals form at small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The problem of temperature quenching is that there is a temperature and even a cooling rate gradient distribution in the samples, which could induce structure defect of the products . Recently using a high‐pressure jump apparatus, Hong et al have prepared many glassy polymers under a dynamic pressurization process—rapid compressing (RC). Different from the most widely used quench cooling techniques, in RC process the melts are solidified by high pressure jump (pressure of the melt can increase from atmospheric pressure to 2.5 GPa in only 20 ms) rather than temperature drop, so it can get rid of the thermal conductivity limitation of polymer materials and proves effective to prepare amorphous polymer materials in large bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of temperature quenching is that there is a temperature and even a cooling rate gradient distribution in the samples, which could induce structure defect of the products . Recently using a high‐pressure jump apparatus, Hong et al have prepared many glassy polymers under a dynamic pressurization process—rapid compressing (RC). Different from the most widely used quench cooling techniques, in RC process the melts are solidified by high pressure jump (pressure of the melt can increase from atmospheric pressure to 2.5 GPa in only 20 ms) rather than temperature drop, so it can get rid of the thermal conductivity limitation of polymer materials and proves effective to prepare amorphous polymer materials in large bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The main peaks in the figures are assigned with reference to the previous report. 21 Figures 1(a) and 1(b) indicate that the structure of Sins (30 C, 0 h) is very similar with that of IS (commercially available product). IS (commercially available product) has been confirmed not to contain S8.…”
Section: Resultsmentioning
confidence: 73%
“…It has been reported that the cleavage of the polymer sulfur chains provides some amount of shorter polymer sulfur chains and S8. 21 According to the reaction mechanism, the variation in the thermal stability and the content ratio of IS with the postheating process are estimated as follows.…”
Section: Effects Of Post-heating Process On Thermal Stability and Conmentioning
confidence: 99%
“…Hong and coworkers found that with RC, the metastable structure can be effectively induced from melt in large volume for many kinds of polymers, such as pure amorphous poly(ethylene terephthalate), poly(ether ether ketone), and poly(lactic acid), and their results proved that RC can even prepare different metastable phase structures and thus improve their properties . Besides, we successfully prepared large bulk amorphous sulfur for the first time using this method, and our recent work indicated that the mesomorphic iPP can also be prepared by rapidly compressing (above 10 MPa s −1 ) the quiescent melt to the pressures higher than 1.0 GPa . To sum up, RC is superior to temperature quenching since the stress equilibrates within the material faster than thermal equilibration, thus the RC method can get rid of thermal conductivity of the melt and would produce products with more uniform structure with larger size .…”
Section: Introductionmentioning
confidence: 85%